FORMATION AND RESEARCH ISSUES OF AXIOLINGUISTICS - D. Lutfullayeva (Modern American Journals, 2025)
This article provides information about one of the new directions of anthropocentric linguistics - axiological studies, its formation, objects of study, subject and basic concepts.
Keywords: Axiolinguistics, value, value attitude to language, axiological consciousness, axiological concept, ethnosemiometric method, value orientation of the individual.